The illusionist - Burger, Neil; Norton, Edward; Giamatti, Paul; Biel, Jessica, 1982-; Sewell, Rufus, 1967-; Marsan, Eddie; Wood, Jake; Fisher, Tom; Pope, Dick, B.S.C; Geraghty, Naomi; Glass, Philip; Millhauser, Steven (20th Century Fox Home Entertainment, 2006)
The acclaimed illusionist Eisenheim has not only captured the imaginations of all of Vienna, but also the interest of the ambitious Crown Prince Leopold. When Leopold's new fiancee rekindles a childhood fascination with Eisenheim, the Prince's interest evolves into obsession. Suddenly the city's Chief Inspector finds himself investigating a shocking crime. But even as the Inspector engages him in a dramatic challenge of wills, Eisenheim prepares for the most impressive illusion yet.